Women in engineering careers - Kahn, Jetty (Mankato, Minn. : Capstone High/Low Books, 1999)
Presents an introduction to engineering followed by brief biographies of the following women engineers: Amy Alving, Cynthia Barnhart, Martha Gray, Jill Morgan, and Karen Zais.
Includes bibliographical references and index.
Keywords: Women engineers -- Biography -- Juvenile literature; Engineers; Women -- Biography